2022
DOI: 10.2106/jbjs.21.00465
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in Care and Outcomes After Total Hip and Knee Arthroplasties

Abstract: Background:There is a paucity of literature on racial differences across a full total joint arthroplasty (TJA) “episode of care” and beyond. Given various incentives, the Comprehensive Care for Joint Replacement (CJR) program in the U.S. may have impacted preexisting racial differences across this care continuum. The purposes of the present study were (1) to assess trends in racial differences in care/outcome characteristics before, during, and after TJA surgery and (2) to assess if the CJR program coincided w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…However, readmission rates among NH Black patients decreased by 24% from 2013 to 2018, narrowing racial disparities [11]. In both studies, PJI was listed among several reasons for readmission, but PJI incidence was not specifically reported [11,12]. In both studies, disparities narrowed over time.…”
Section: The Incidence Of Pji In Nh Black Individuals Was Twice That ...mentioning
confidence: 91%
See 4 more Smart Citations
“…However, readmission rates among NH Black patients decreased by 24% from 2013 to 2018, narrowing racial disparities [11]. In both studies, PJI was listed among several reasons for readmission, but PJI incidence was not specifically reported [11,12]. In both studies, disparities narrowed over time.…”
Section: The Incidence Of Pji In Nh Black Individuals Was Twice That ...mentioning
confidence: 91%
“…Similarly, a retrospective analysis of national Medicare claims data on 1,483,221 TJAs performed from 2013 to 2018 found that NH Black adults were 38% more likely to have 90-day readmission compared to NH White patients in 2013. However, readmission rates among NH Black patients decreased by 24% from 2013 to 2018, narrowing racial disparities [11]. In both studies, PJI was listed among several reasons for readmission, but PJI incidence was not specifically reported [11,12].…”
Section: The Incidence Of Pji In Nh Black Individuals Was Twice That ...mentioning
confidence: 93%
See 3 more Smart Citations